2014
DOI: 10.4236/fns.2014.52029
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Prefrontal Cortex to Pleasant and Aversive Taste Using Functional Near-Infrared Spectroscopy

Abstract: The aim of the study was to investigate the representation of taste in human prefrontal cortex (PFC), in particular, to compare the representation of a pleasant and an aversive taste using functional near-infrared spectroscopy (fNIRS), so as to obtain further understanding of the taste preference mechanism. The pleasant stimulus used was sweet taste (10% sucrose), and the unpleasant stimulus was sour taste (1% critic acid). Based on event-related design, the experiments were performed with 16 healthy volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…fNIRS is a recent advancement in neuroimaging and provides topographical assessment of real-time regional cortical hemodynamic changes [92•] which could be useful to investigate brain activation during cognitive tasks such as the Stroop, food Stroop, and go/no-go task. Recent fNIRS studies on eating behavior have reported decreased activation in the DLPFC induced by sweet and sour taste stimuli [93]…”
Section: Areas For Future Studymentioning
confidence: 99%
“…fNIRS is a recent advancement in neuroimaging and provides topographical assessment of real-time regional cortical hemodynamic changes [92•] which could be useful to investigate brain activation during cognitive tasks such as the Stroop, food Stroop, and go/no-go task. Recent fNIRS studies on eating behavior have reported decreased activation in the DLPFC induced by sweet and sour taste stimuli [93]…”
Section: Areas For Future Studymentioning
confidence: 99%
“…fNIRS is a non-invasive neuroimaging technique that uses near-infrared light to measure hemodynamic signals reflecting changes in hemoglobin concentrations in the brain. It is well-suited for measuring brain activation during real-world tasks and has been used successfully in previous sensory studies such as taste (Okamoto and Dan, 2007 ; Hu et al, 2014 ), flavor (Okamoto et al, 2006 ; Hasegawa et al, 2013 ), and tactile stimuli (Hong et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the sense of taste perceives both harmful and beneficial things, all basic tastes are classified as either aversive or appetitive depending on their effect on the body. Thus, salty, sweet, and umami are often associated with an intake of essential nutrients, while bitter and sour indicate potentially harmful substances (Hu, Kato, & Luo, 2014). Thus, the emotions evoked by taste are related to food regulation, dietary balance, and harm avoidance.…”
Section: Introductionmentioning
confidence: 99%